Audit of the Tejamari Village Service Website Information System Using the COBIT 5 Framework - Aldiyanti, Fitri; Auliana, Sigit; Dwiki Putra Aryono, Gagah (INOVTEK Polbeng - Seri Informatika, 2025)
Digital transformation in public services at the village level requires systematic evaluation to ensure the effectiveness of information technology implementation. The research gap is identified from the lack of studies auditing village service information systems using a combination of DSS01 and BAI01 domains of the COBIT 5 framework. This study contributes to filling the gap in the literature by auditing the website-based service information system of Tejamari Village, Serang Regency, using the COBIT 5 framework, focusing on the DSS01 and BAI01 domains. The research methodology adopts a qualitative approach with a case study design using the COBIT 5 Process Assessment Model across seven systematic stages. Data triangulation was conducted through structured observations, in-depth interviews with key stakeholders, and comprehensive document analysis. The scope of the study is limited to the two specified COBIT 5 domains, with an evaluation period restricted to one month at a single location. The evaluation results show that both domains are at capability level 1, with DSS01 scoring 46.66% and BAI01 achieving 72.60%. The findings identify critical deficiencies in procedure documentation, operational standardisation, and IT resource management. The system reached level 0 with "Fully Achieved" status but did not meet the 85% threshold required to progress to the next level. The theoretical contribution of this research enriches the literature on information system audits in public services through a domain-specific COBIT 5 approach, while the practical contribution provides a roadmap for improving digital village service quality through recommendations for procedural standardization and resource optimization.